Innovative Procedure for Intrinsically Safe Storage Vessel Design: the Case Study on Hydroxylamine Decomposition - Giuseppe Andriani; Paolo Mocellin; Chiara Vianello; Ernesto Salzano; Gianmaria Pio (Chemical Engineering Transactions, 2025)
Materials prone to exothermic decomposition reactions can generate severe concerns during storage activity on an industrial scale. Indeed, due to the large amount of handled chemicals, the consequences of runaway phenomena induced by improper management of the generated thermal energy could be devastating for the environment, people and assets. In the case of less extreme conditions, runaway reactions can be avoided, even if thermal degradation is activated by deviation in external conditions. Nevertheless, significant impacts on economic profitability and asset integrity should be considered. Indeed, during thermal degradation, valuable chemicals react and are converted into products that, in most cases, cannot be commercialised and require treatment and disposal as waste. In this view, the present work proposed an innovative procedure for simultaneously evaluating the safety and economic aspects, leading to a more sustainable and consistent way to conduct and design plants and equipment. This procedure is based on the Frank-Kamenetskii theory of self-heating (FKT), which can be employed for an intrinsically safe design of storage vessels handling molecules prone to exothermic decomposition reactions. However, in its original formulation, the FKT is not suitable for considering the effects of the activation energy of a reaction nor the consequence of reactant conversion on the overall self-heating dynamic. Under these premises, this article reports an expanded FKT to evaluate the effects of a simultaneous resolution of the energy and mass balance on the numerical outcomes of the theory. The obtained approach was applied to design storage vessels containing materials prone to exothermic degradation reactions. For the sake of validation purposes, numerical predictions obtained in this work were compared with experimental data available in the current literature on the decomposition of aqueous solutions containing hydroxylamine salt, showing an excellent agreement. Different compositions and external boundary conditions were tested to this scope. Therefore, the adopted procedure can be considered for the sizing of equipment containing chemicals, to efficiently dispose of the generated thermal energy, avoiding runaway conditions induced by a poorly managed self-heating mechanism.